2013
DOI: 10.1097/ta.0b013e31829d3504
|View full text |Cite
|
Sign up to set email alerts
|

Early application of airway pressure release ventilation may reduce mortality in high-risk trauma patients

Abstract: Systematic review, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 98 publications
(115 citation statements)
references
References 37 publications
2
112
0
1
Order By: Relevance
“…Indeed, clinical studies have shown that early application of LV t ventilation with various levels of PEEP signifi cantly reduces the incidence of ARDS, presumably by reducing tissue overdistension in areas of stress concentration and by preventing RACE. 20,24,26,39,40 However, a recent study demonstrated that LV t alone applied to the normal lung during surgery in patients at high risk for developing ARDS was associated with increased mortality 28 and that LV t with high but not low PEEP increased postoperative pulmonary complications. 29 In contrast, Futier et al 26 showed that the combination of LV t , PEEP, and RMs signifi cantly reduced acute respiratory failure and mortality in patients undergoing major surgery.…”
Section: T Peep and Rmsmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, clinical studies have shown that early application of LV t ventilation with various levels of PEEP signifi cantly reduces the incidence of ARDS, presumably by reducing tissue overdistension in areas of stress concentration and by preventing RACE. 20,24,26,39,40 However, a recent study demonstrated that LV t alone applied to the normal lung during surgery in patients at high risk for developing ARDS was associated with increased mortality 28 and that LV t with high but not low PEEP increased postoperative pulmonary complications. 29 In contrast, Futier et al 26 showed that the combination of LV t , PEEP, and RMs signifi cantly reduced acute respiratory failure and mortality in patients undergoing major surgery.…”
Section: T Peep and Rmsmentioning
confidence: 99%
“…24,[31][32][33][34] In other words, protection against the development of ALI is conferred by much more than simply the values of V t , plateau pressure, and PEEP that are used; the durations over which these parameters are applied also determine whether lung injury will progress. Mode acronyms such as APRV or CMV, thus, do not encompass all the features of a mechanical breath that determine its injurious or protective impact because the temporal details of the mechanical breath can be critical to this impact.…”
Section: Lm (Surfactant Sloughed Into the Alveolar Lumen) And Increasmentioning
confidence: 99%
See 3 more Smart Citations